EFEKTIVITAS PENYUNTIKAN FSH SECARA SUBKUTAN DAN INTRAMUSKULAR TERHADAP RESPON SUPEROVULASI SAPI SIMENTAL - Djunaedi, Mohammad; Handarini, Ristika; Zamanti, Deasy (Universitas Djuanda Bogor, 2018)
Superovulation is a necessary technique to produce large number of embryos for embryo transfer. Hormonal treatment is superovulation methode can be done by implant CIDR and injection of Follicle Stimulating Hormone (FSH). Experiment were carried out to observe the effectiveness of subcutaneous and intramuscular FSH injections on superovulation response in simmental cattle. All animal (n=10) were treated with intravaginal CIDR implant before FSH injection. Studies were devided into two experiment. In experiment 1 (P1), 400 mg FSH (diluted in 4 ml sterile diluent) injected in five simmental cattle by single subcutan injection. In experiment 2 (P2), 400 mg FSH (diluted in 20 ml sterile diluent) injected in five simmental cattle by twice daily intramuscular injection over 4 day in decreasing doses. The number of corposa luteal (CL), total embryos collected, and total transferable embryos were observed in this experiment. Data were analyzed by T-test method. The result showed that effectiveness of single subcutan FSH injection were significanthy different (P < 0,05) than intramuscular FSH injection superovulation with single subcutan FSH injetcion is easier than twice daily intramuscular injection in decreasy dose. In conclusion the average of CL (21,4 Â± 3,6) and number of tranferable embryo (71,96 %) of the single subcutan FSH injection tended to be better than intramuscular FSH injection. Single subcutan FSH injection more efficient than intramuscular FSH injection. Single subcutan injection can decreasing sterss level in the cattle and be easier in handling the cattle during the experiment.Keywords: Simmental cattle, FSH, superovulation, single subcutan injection, intramuscular injection.